The Effectiveness of Incentives on Completion Rates, Data Quality, and Nonresponse Bias in a Probability-based Internet Panel Survey. Issue 2 (May 2020) - Stanley, Marshica; Roycroft, Jessica; Amaya, Ashley; Dever, Jill A.; Srivastav, Anup
Previous research has shown that increasing the size of incentives can increase response rates for probability-based, cross-sectional surveys. However, the effects of incentives on web panels have not been extensively studied. We sought to answer the question: What is the effect of larger, postpaid incentives on (1) response, (2) data quality, and (3) nonresponse bias for individuals in a web panel? We analyzed data from the 2015 and 2016 National Internet Flu Survey, a survey that uses the GfK KnowledgePanel® as its sampling frame. We compare panel members who received a postpaid, standard 1, 000-point (the equivalent of US1) incentive in 2015 to panelists who received a larger, 5, 000-point (the equivalent of US5) incentive in 2016. We found that larger incentives were associated with increased interview completion rates with minimal impact on data quality or bias.